2021
DOI: 10.1007/jhep05(2021)015
|View full text |Cite
|
Sign up to set email alerts
|

Light-ray operators, detectors and gravitational event shapes

Abstract: Light-ray operators naturally arise from integrating Einstein equations at null infinity along the light-cone time. We associate light-ray operators to physical detectors on the celestial sphere and we provide explicit expressions in perturbation theory for their hard modes using the steepest descent technique. We then study their algebra in generic 4-dimensional QFTs of massless particles with integer spin, comparing with complexified Cordova-Shao algebra. For the case of gravity, the Bondi news squared term … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 129 publications
(215 reference statements)
1
16
0
Order By: Relevance
“…There it was shown that a Poissonian distribution of the cut reggeons naturally explain the AGK cancellation, and this actually inspired part of the ideas developed in this work. Furthermore, the set of infinite amplitude relations we found must have some nontrivial overlap with the ones related to soft theorems [37,97], which in general are also valid beyond the classical regime. It would be interesting to explore this further.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…There it was shown that a Poissonian distribution of the cut reggeons naturally explain the AGK cancellation, and this actually inspired part of the ideas developed in this work. Furthermore, the set of infinite amplitude relations we found must have some nontrivial overlap with the ones related to soft theorems [37,97], which in general are also valid beyond the classical regime. It would be interesting to explore this further.…”
Section: Discussionmentioning
confidence: 85%
“…This is crucial to obtain a well-behaved scattering angle at high energies [33], as was proven by a direct calculation of radiation reaction effects [11,12,[34][35][36]. A similar principle holds as well for less inclusive observables like gravitational energy event shapes [37]. 1 We would like to understand the exact structure of the final semiclassical state, including classical radiation.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations